An experimental test of control theory‐based interventions for physical activity. Issue 4 (6th October 2016) - Prestwich, Andrew; Conner, Mark; Hurling, Robert; Ayres, Karen; Morris, Ben
Abstract : Objectives: To provide an experimental test of control theory to promote physical activity. Design: Parallel groups, simple randomized design with an equal chance of allocation to any group. Methods: Participants not meeting recommended levels of physical activity but physically safe to do so ( N = 124) were recruited on a UK university campus and randomized to goal‐setting + self‐monitoring + feedback (GS + SM + F, n = 40), goal‐setting + self‐monitoring (GS + SM, n = 40), or goal‐setting only (GS, n = 44) conditions that differentially tapped the key features of control theory. Accelerometers assessed physical activity (primary outcome) as well as self‐report over a 7‐day period directly before/after the start of the intervention. Results: The participants in the GS + SM + F condition significantly outperformed those in the GS condition, d = 0.62, 95% CI d = 0.15–1.08, and marginally outperformed those in the GS + SM condition in terms of total physical activity at follow‐up on the accelerometer measure, d = 0.33, 95% CI d = −0.13 to 0.78. The feedback manipulation (GS + SM + F vs. GS + SM and GS) was most effective when baseline intentions were weak. These patterns did not emerge on the self‐report measure but, on the basis of this measure, the feedback manipulation increased the risk that participants coasted in relation to their goal in the first few days of the intervention period. Conclusions: Using behaviour change techniques consistent with control theory can lead to significant short‐term improvements on objectively assessed physical activity. Further research is needed to examine the underlying theoretical principles of the model. Statement of contribution What is already known on this subject? Interventions incorporating more techniques that are consistent with control theory are associated with larger positive changes in health behaviours and related outcomes (see reviews by Dombrowski et al ., 2012 ; Michie et al., 2009 ). However, none of the studies included in these reviews were explicitly based on control theory (see Prestwich et al ., 2014 ). What does this study add? This study is the first experimental test of the cumulative effects of behaviour change techniques as proposed by control theory. Intervening on all aspects of the feedback loop noted by control theory leads to more change; however, the risk that some participants coast in relation to their set goal is significant. This approach increased physical activity more in those with weaker intentions pre‐intervention.